Conflict and conversion in sixteenth century central Mexico the Augustinian War on and beyond the Chichimeca frontier - Jackson, Robert H. (Leiden Brill, 2013)
In the sixteenth century Franciscan, Dominican, and Augustinian missionaries attempted to convert the native populations of central Mexico. The native peoples generally viewed the new religion in terms very different from that of the missionaries. As conflict broke out after 1550 as Spaniards invaded the Chichimeca frontier (the frontier between sedentary and nomadic natives), the missionaries faced new challenges on both sides of the frontier. Some sedentary natives resisted evangelization, and the missionaries saw themselves in a war against Satan and his minions. The Augustinians assumed a pivotal role in the evangelization campaign on both sides of the Chichimeca frontier, and employed different methods in the effort to convince the natives to embrace the new faith and to defeat Satan's designs.They used graphic visual aids and the threat of an eternity of suffering in hell to bring recalcitrant natives, such as the Otomi of the Mezquital Valley, into the fold.
CSSP-7980 donated by Brill Publishers through SPi Global Foundation, Inc.
Keywords: Augustinians -- Missions -- Mexico -- History -- 16th century; Chichimecs -- Wars, 1550-1591.; Chichimecs -- Missions -- History -- 16th century; Chichimecs -- Social conditions; Mexico -- History -- Spanish colony, 1540-1810.